PENDAMPINGAN DESA BERKELANJUTAN PENGOLAHAN SAMPAH ORGANIK MENJADI KOMPOS DI DESA DALUNG KECAMATAN CIPOCOK KOTA SERANG - Arlofa, Nina Arlofa; Febriasari, Arifina (Universitas PGRI Yogyakarta, 2023)
The waste produced in the city of Serang reaches 360 tons/day, while the waste that can be transported by the Environmental Service (DLH) in the town of Serang to the Final Disposal Site (TPA) is only around 70-80 tons/day. In general, waste management in the community is by burning, throwing it into the river, or collecting it in trash cans to be then taken by the garbage officer and disposed of at the TPA. The same thing also happened in Dalung village, the waste generated from community activities was burned or collected into trash bins to be then taken by officers to be disposed of in the waste landfill. Burning waste causes pollution, and waste disposal in landfill causes degradation of cleanliness and environmental quality due to methane gas which causes global warming, where the gas has a destructive power 23 times stronger than carbon and other gases such as SO2 gas which causes odor. Organic waste can be processed into liquid fertilizer, compost, or methane gas. The implementation of community activities aims to increase public knowledge about the importance of waste management, layout arrangements, and the manufacture of organic and inorganic waste bins as well as training in composting. keywords: fermentation, compost, organic, rubbish